Dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in patients with chronic coronary artery disease (CAD) - current state of knowledge and perspective for further research - Bochenek, Hubert; Bielicka, Anna; Bzoma, Michał; Gugulska, Julia; Czerepak, Irmina; Kapij, Marcin; Niewczas, Karolina; Brzozowska, Adrianna (Journal of Education, Health and Sport, 2025)
Introduction and purpose: aa Chronic coronary artery disease (CAD) is a prevalent condition affecting millions of people worldwide, significantly reducing quality of life and increasing the risk of myocardial infarction (MI). Percutaneous coronary intervention (PCI), often combined with stent implantation, is a cornerstone of CAD treatment. However, it induces a prothrombotic state, necessitating dual antiplatelet therapy (DAPT) to mitigate the risk of thrombosis and MI. Despite its established role, the optimal duration and specific composition of DAPT still remain under investigation. This article aims to summarise current knowledge on DAPT and highlight gaps requiring further research. Description of the state of knowledge: DAPT typically involves acetylsalicylic acid (ASA) 75 mg and clopidogrel 75 mg for 6 months after PCI. While this is effective in reducing thrombotic events, it also increases bleeding risk. Current European Society of Cardiology (ESC) guidelines recommend tailoring DAPT duration and composition based on individual patient risk factors for bleeding and ischemia. Alternatives include shortening DAPT to 1–3 months for patients with high bleeding risk or intensifying it with stronger antiplatelet agents like ticagrelor or prasugrel for those at high ischemic risk. However, evidence supporting these alternatives remains limited, and require further investigation. Emerging options, such as vorapaxar, present additional potential, but also require further validation. Summary: CAD management through PCI relies heavily on effective DAPT. Current strategies emphasize balancing ischemic and bleeding risks in optimising treatment. Although significant progress has been made, optimal DAPT regimens for specific patient groups remain uncertain, particularly in cases of shortened or intensified therapy. Continued research is crucial to refine treatment protocols and improve patient outcomes.